A feeding Duke-of-York interaction of tone and epenthesis in Arapaho. Issue 1 (14th August 2019) - Gleim, Daniel
Abstract : In the Algonquian language Arapaho, epenthetic vowels only show up if they can attract an underlying floating high tone. I argue that this co-dependency of tone and epenthesis should not be analysed as tone-triggered epenthesis (which has been claimed not to exist, Blumenfeld 2006 ). Instead, I conclude that the pattern should be analysed as an opaque interaction of epenthesis, tone assignment and vowel deletion. Since the epenthetic vowel is first inserted and later deleted, this interaction constitutes an instance of what is called a Duke-of-York gambit or derivation – more precisely a feeding Duke-of-York derivation, because the epenthetic vowel leaves traces behind. This type of opacity is conceptually intriguing for both constraint and rule-based models of phonology, but proves especially problematic for Optimality Theory (OT). I claim that the best analysis with constraint-based frameworks lies in the adoption of Stratal OT (Kiparsky 2000 ; Bermúdez-Otero 2011 ). Epenthesis applies in a first stratum where the epenthetic vowel is involved in segmental processes, deletion then applies on a higher stratum.